Improving knowledge, attitudes and beliefs: a cross-sectional study of postpartum depression awareness among social support networks during COVID-19 pandemic in Malaysia - Suleiman Alsabi, Rania Nafi’; Zaimi, Alif Firdaus; Sivalingam, Thanusha; Ishak, Nurul Nazirah; Alimuddin, Aishah Siddiqah; Dasrilsyah, Rima Aggrena; Basri, Nurul Iftida; Mohd Jamil, Amilia Afzan (BioMed Central, 2022)
Background: Postpartum depression (PPD) is the most prevalent mental health disorder after childbirth, notably during the COVID-19 pandemic. In addition, PPD is known to have a long-term influence on the mother and the newborn, and the role of social support network is crucial in early illness recognition. This study aims to evaluate the social support networks’ level of knowledge, attitudes and beliefs regarding PPD and examine their sociodemographic variables and exposure to the public information relating to PPD during the COVID-19 pandemic in Malaysia. Methods: A cross-sectional study was conducted via an online Google Form disseminated to people in Klang Valley through WhatsApp, Email, Facebook, Instagram and other available social media among postpartum women’s social support networks aged 18 years and living in the Klang Valley area (N = 394). Data were collected from 1 March to 5 July 2021 and analysed using the Mann–Whitney U-test and generalised linear mixed models. Results: During the COVID-19 epidemic in Klang Valley, most participants had good knowledge, negative attitudes and awareness of PPD. Marital status, gender and parity all had significant correlations with the amount of awareness regarding PPD. Ethnicity, gender, parity and educational level showed significant association with attitude towards PPD. No significant relationship was noted between sociodemographic variables and PPD beliefs. Public awareness of PPD was also associated with knowledge and attitude towards it. Conclusions: A significant positive knowledge, negative attitude and negative awareness level of PPD exist among social support networks for postnatal women. However, no significant effect of belief on PPD awareness level was noted. Implications: Insight campaigns and public education about PPD should be conducted to enhance postnatal mothers’ awareness and knowledge. Postnatal care, mental check-ups and counselling sessions for the new mothers are recommended. In future studies, a closer assessment of postpartum social support, variances and similarities across women from diverse racial/ethnic origins is critical. Strengths and limitations: This cross-sectional study is one of the early studies on the area of PPD in the Malaysian region during COVID-19. Numerous data have been collected using low-cost approaches using self-administered surveys through Google Forms in this research.